Bioassay Method Development to Test Sitophilus oryzae Sensitivity against Phosphine - Harahap, Nafsiyah Agustina; Witjaksono, Witjaksono; Martono, Edhi; Trisyono, Y. Andi (Jurnal Perlindungan Tanaman Indonesia, 2023)
Sitophilus oryzae is a cereal product pest found in warehouses. The presence of this pest negatively impacts the quality and quantity of stored rice. The common method used to control warehouse pests is fumigation. However, frequent use of insecticides will trigger resistance within target pest populations. This study aimed to develop a bioassay method based on the Food Agriculture Organization (FAO) protocols and modify bioassay protocols to determine S. oryzae susceptibility of populations collected from traditional markets across Yogyakarta. Field populations were collected from eight traditional markets in Yogyakarta (Lempuyangan Market [Kapanewon Danurejan], Kranggan Market [Kapanewon Jetis], Caturtunggal Market [Kapanewon Depok], Godean Market [Kapanewon Godean], Imogiri Market [Kapanewon Imogiri], Pleret Market [Kapanewon Pleret], Kasihan Market [Kapanewon Lendah], and Brosot Market [Kapanewon Galur]). The reference population was obtained from the Southeast Asian Regional Centre for Tropical Biology(SEAMEO BIOTROP). The bioassay was carried out following FAO protocols by using a glass jar fumigation chamber (volume 2 L) which was a modification of the desiccator of FAO recommended method number 16. This test used the lowest testable dose for this method: 0.01 × 10-2 mg/2L or 0.5 × 10-2 µg/L tested on 100 imagoes which were divided into five replications and obtained 100% mortality on the second day (48 hours). Results showed that the FAO fumigation chamber method could not be used in the test, so modifications were carried out to determine tested doses by changing the volume of the fumigation container. The test used three container volumes, including 20, 60, and 80 L. Result from 20 L container showed 82-100% mortality, 60 L containers showed 69-100% mortality, and 80 L containers showed 24-79% mortality. Results from 80 L container was suitable for the bioassay because it was able to test the lowest dose on reference insects. Eight doses ranging from 0.125 to 1.625 × 10-2 µg/L, and an untreated control were used to determine the LD50 of phosphine on each population. Insects were fumigated for 48 hours and then removed to observe mortality. The LD50 of the reference population was 0.27 × 10-2 µg/L while 0.29-0.54 × 10-2 µg/L for field populations. These findings indicate that S. oryzae populations collected from traditional markets in Yogyakarta were still susceptible to phosphine.